2019
DOI: 10.1055/s-0039-1694041
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Effects of Physician Gaze on Patient Satisfaction in the Setting of Electronic Health Records

Abstract: This study aims to determine the amount of time ophthalmologists using electronic health records (EHRs) spend looking at the patient and its correlation on patient satisfaction. This prospective cohort study examined 67 patients seeking care at two different ophthalmology clinics. Videos of entire office visits were recorded and each video was graded for amount of time spent by physicians gazing at the patient, computer, paper medical records, or other areas. Videos were also graded for the amount of time exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…(1,5,15) The factors that affect the doctor-patient relationship domain of the patient satisfaction include maintenance of eye contact and gaze time, by the physicians. (16,17) While Shaaranai et al reported that majority of the patients believed that Electronic Health Records (EHR) improved the efficiency of the physicians,(18) doubts over the competence and trust deficit was expressed towards those physicians who used digital devise. Competence of the treating physician, as perceived by the patient, is one among the four attributes of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…(1,5,15) The factors that affect the doctor-patient relationship domain of the patient satisfaction include maintenance of eye contact and gaze time, by the physicians. (16,17) While Shaaranai et al reported that majority of the patients believed that Electronic Health Records (EHR) improved the efficiency of the physicians,(18) doubts over the competence and trust deficit was expressed towards those physicians who used digital devise. Competence of the treating physician, as perceived by the patient, is one among the four attributes of patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Specialists may be more tempted to gaze or type into the electronic health record during a virtual conversation. 24 Even if patient satisfaction increases, other clinical outcomes remain unknown. 25 Virtually caring for a patient is like virtually driving a car; the car seat is actually stationary and the outcomes are qualitatively different from, although not necessarily superior or inferior to the experience of real driving.…”
Section: Virtual Patient Visitsmentioning
confidence: 99%
“…Clinically unstable conditions might be missed. Specialists may be more tempted to gaze or type into the electronic health record during a virtual conversation 24 . Even if patient satisfaction increases, other clinical outcomes remain unknown 25 .…”
Section: Clinical Judgement In Specialist Medicinementioning
confidence: 99%